Edukasi untuk Meningkatkan Pengetahuan tentang Makanan Bergizi pada Ibu Hamil dalam Pencegahan Stunting - Hastuti, Lidia; Wahyuni, Tri; Mardiyani, Ridha; Mumtahanah, Al; Khairillah, Yuyun Nisaul; Riwayati, Riwayati (Jurnal Abdimas Kesehatan (JAK), 2024)
The direct causes of stunting include inadequate nutritional intake and infectious diseases. Lack of awareness and knowledge of women of childbearing age, especially pregnant women, regarding the importance of nutritious food and types of nutritious food during pregnancy, can contribute to stunting. The solution offered is the provision of health education, this activity will be aligned with the government. Activities were carried out synergistically in one of the villages, namely Bange Village with the participation of the Community Health Center, District Head, Village Head, and nutrition practitioners. The objective of this study is to increase the knowledge and understanding of pregnant women about the importance of consuming nutritious food during pregnancy to prevent stunting in their babies. Beside it, to conduct the health promotion at the community base by providing health education about the importance of nutritious food and nutritious foods for pregnant women and their processing. Before the activity was carried out, a pre-test was carried out and after that a post-test was given to evaluate the results of the health education carried out. Evaluation of activities by assessing the comparison of pre-test scores and post-test scores. After the health education activities are completed, pregnant women are given additional food packages. Health education about the importance of nutritious food and nutritious foods for pregnant women and their processing is proven to increase knowledge.